593. A Nationwide Assessment of Predictive Factors for Provision of Continuity of Care Resources for HIV-Positive Detainees in ICE Health Service Corps-Staffed Facilities, 2015 and 2017. (26th November 2018) - Mishreki, Alexandra; Brodine, Stephanie; Yang, Ming; Lederman, Edith
Abstract: Background: Continuity of care (CoC) is paramount to the successful management of patients with human immunodeficiency virus (HIV), and is uniquely challenging when patients are mobile. Over the past several years Immigration and Customs Enforcement Health Service Corps (IHSC) has increased training and education for providers regarding the provision of CoC. The objective of this study was to evaluate the impact of these efforts by assessing provision of and factors associated with CoC counseling to HIV-infected detainees in 2015 as compared with 2017. Methods: This retrospective analysis reviewed electronic health records of detainees with confirmed HIV infection detained at any of the 21 IHSC-staffed nationwide facilities between January–December 2015 and January–August 2017. Using SAS software V.9.3, odds ratios, 95% CI, chi-square, univariate and multiple logistic regression analyses were utilized to assess and compare relationships between independent variables and CoC for 2015 and 2017. Results: Five hundred and eight HIV-infected detainees were identified; they were predominately male (88.4%), born in Mexico (37%), generally had CD4 counts >200 (86.2%) and had an established diagnosis of HIV prior to entering custody (94.1%). Among all primary variables assessed for predictive association to CoC, female gender and infectious disease (ID) consultation were statistically significant ( P = 0.0.0058, 0.0085) after adjusting for all other variables. Compared with all other detainees, our sample was in custody twice as long (61 days vs. 31 days, P < 0.001). In 2015 and 2017, 91% of detainees received ART during custody, and CoC prior to release nearly doubled from 29.4% in 2015 to 59.6% in 2017. Conclusion: Discussing CoC with ICE detainees is imperative given their increased risk for treatment interruption. Our results emphasize that (i) CoC discussion should happen early in custody stay as most detainees have left our care system within two months of entry, (ii) providers should be aware of possible bias during counseling and offer the same level of CoC discussion regardless of gender or clinical parameters. Questions prompting and reminding providers to have CoC discussions should be included in HIV-specific templates during the initial health assessment. Disclosures: All authors: No reported disclosures.